KEKUATAN DAN KELEMAHAN JURUSAN ILMU KOMUNIKASI UIN ALAUDDIN MAKASSAR DALAM PENCAPAIAN VISI MISI - Mudzhira Nur Amrullah (Jurnal Komodifikasi, 2017)
Organization for Economic Co-operation Development (OECD) report, "Indonesia will become the country with the fifth highest number of undergraduate courses in the world by 2020". This data is a projection of Indonesia's efforts to increase the number of college graduates each year. Whereas on the other hand, the absorption of undergraduate graduates in Indonesia is relatively slow. Observing the OECD report, there should be a warning to managers and providers of higher education to be more alert and responsive to change and development needs of the workforce that is highly dynamic, however, because the college is still valued as an important pillar of nation building. Department of Communication Studies Faculty of Da'wa and Communication UIN Alauddin Makassar is currently packing oriented courses nationwide with KKNI learning outcomes as a reference. All that is done to realize the vision and mission. The Department's strengths and weaknesses need attention. Laboratory facilities that became the strength of Communication Studies, namely: Lab. Radio, Lab. Broadcasting, Multimedia Lab, Lab. Graphic Design and Photo Studio with very complete equipment for the size of a relatively new educational institution (Department of Communication Science began actively in 2008) needs to be maximized utilization by completing a reliable laboratory. Elements of existing weakness need to be minimized. The lack of human resources, especially the laboratory management, limited room facilities with large number of students, the lack of cooperation between the departments of I.Communication with institutions related to Communication Science, and Curriculum that still needs to be addressed by the Communication Science Faculty of Da'wah and Communication UIN Alauddin Makassar. Institutions will compete with the number of Islamic Universities that have Communication Studies, State and Private Universities that have much earlier had the same majors. It also can not be ignored. Therefore, Department of Communication Science Faculty of Da'wa and Communication need to have concentrations that can be superior, have more value from the same Department.